Equivalent circuit model of antenna array utilizing an Archimedean spiral sequential feed network for c-band applications - Ahmad, Khalid Subhi; Che Seman, Fauziahanim; Hamzah, Shipun Anuar; Alhassoon, Khaled; Saeidi, Tale; Zakaria, Zahriladha; Al Gburi, Ahmed Jamal Abdullah (Electromagnetics Academy, 2024)
This paper introduces the configuration of a microstrip antenna array with a new Archimedean spiral sequential feed network (SSFN) for the upper half of the C-band application. The Archimedean SSFN mechanism uses four circular patch elements to structure the proposed antenna array. The optimized reflection loss (S11) of the proposed SSFN mechanism was obtained by tuning the dimensions of each transformer and then connected with an antenna array. Aiming to make the suggested antenna array compact in size, bending feed lines were utilized. The antenna array is designed with the overall physical dimensions of 75 mm × 75 mm × 1.575 mm, with an electrical size of 1.85λo mm, 1.85λo mm, 0.038λo at a frequency of 7.43 GHz. An equivalent circuit model (ECM) is designed and analyzed to verify the proposed Archimedean SSFN and the designed antenna array. Reflection losses of SSFN and microstrip spiral antenna array (SAA) were confirmed with the suggested circuit model utilizing Computer Simulation Technology (CST) Microwave Studio and Applied Wave Research (AWR) Microwave Office software. According to the empirical results, the SAA has a reflection loss bandwidth of 2.08 GHz (6.15–8.23 GHz) and a maximum gain of 10.2 dBi at 7.43 GHz. The axial ratio (AR) of the proposed antenna covers a bandwidth of 1.6 GHz (6.2–7.8 GHz), which is approximately 22.85% of the entire bandwidth. These results demonstrate a perfect agreement between the simulated and measured outcomes, making the suggested SAA suitable for the C-band wireless application.